Tindakan Balasan atas Persona Non Grata terhadap Pejabat Diplomatik Amerika Serikat oleh Rusia Berdasarkan Vienna Convention on Diplomatic Relations 1961 - Ratu Sheeva Amadea; Danial Danial; Surya Anom (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2023)
Between states definitely need one another. Because of these needs, countries create a relationship and it is diplomatic relations. Therelationship was not always good between those countries who met with expulsions, officials commonly referred to as non grata that people often met. The identification of the problem in this research is, Is the Russian Government's Countermeasures Against US Diplomatic Officials Justified by the 1961 Vienna Convention? Is Russia's Application of the Persona Non Grata Principle to US Diplomatic Officials a Violation of the 1961 Vienna Convention?Is Russia's Application of the Persona Non Grata Principle to United States Diplomatic Officials a Violation of the 1961 Vienna Convention? This research uses the Theory of State Sovereignty and the Principle of Reciprocity. The method used in this research is normative juridical method which uses secondary data. Uses descriptive analytics, and further of data collection technique using library research which analyses with qualitative analysis by describing or explaining the subject or object of research. The results of this research are first, Russia's countermeasures carried out by the Russian government against United States diplomatic officials cannot be justified by the 1961 Vienna Convention. Because countermeasures in the form of persona non grata are specifically regulated in Article 9 that states are allowed to carry out persona non grata without any reason and this must be done based on the sovereignty of the country and the principle of reciprocity. Second, the declaration of persona non grata by Russia to United States Diplomatic Staffs lies in several violations of the 1961 Vienna Convention, because in declaring persona non grata stated by Article 9 in means without reason, a state must pay attention to other provisions stipulated in the 1961 Vienna Convention. Basically, Russia abuses the declaration of persona non grata against a sending country because a sending country must be based on several criteria for violating actions and paying attention to other provisions of the Convention in order to maintain relations between countries and international peace.